Analysis of pathogen distribution and serum procalcitonin level alterations in patients with type 2 diabetes mellitus complicated by urinary tract infections - Pu, Yuan; Teng, Yirong; Li, Yinghua; Zhou, Yunchun; Gao, Ming; Chen, Xianglan; Yan, Zilin; Li, Xia; Wei, Rong; Teng, Zhaowei (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the distribution and antibiotic resistance of pathogens in patients with Type 2 Diabetes Mellitus (T2DM) complicated by Urinary Tract Infections (UTIs), and to explore the value of serum Procalcitonin (PCT) level alterations in the diagnosis and assessment of disease severity in these patients.MethodsThis retrospective analysis included 100 patients with T2DM complicated by UTIs admitted to the Sixth Affiliated Hospital of Kunming Medical University between January 2021 and August 2024, who constituted the Infection group. A control group, the T2DM group, consisted of 100 patients with T2DM without UTIs. Key demographic data were retrospectively analyzed and evaluated. Bacterial isolation and identification, along with antimicrobial susceptibility testing using an automated analyzer, were performed to determine the distribution and antimicrobial resistance profiles of the isolated pathogens. Serum PCT levels were measured using electrochemiluminescence immunoassay. Receiver Operating Characteristic (ROC) curve analysis was used to evaluate the diagnostic value of PCT for T2DM complicated by UTIs. The optimal cutoff value was calculated using the Youden index derived from the ROC curve.Results146 pathogenic strains were isolated from the 200 submitted specimens. Gram-negative bacteria accounted for 66.44% (n=97), Gram-positive bacteria for 14.38% (n=21), and fungi for 19.18% (n=28). Escherichia coli was the most common pathogen. Antimicrobial susceptibility testing revealed high resistance rates of E. coli to levofloxacin and ampicillin, while no resistance was observed to amikacin and tigecycline. Candida glabrata exhibited high resistance to itraconazole, but no resistance to 5-flucytosine, fluconazole, or voriconazole. Serum PCT levels were significantly elevated in the infection group compared to the T2DM group (P< 0.05). ROC curve analysis revealed that the area under the curve (AUC) for PCT in diagnosing T2DM complicated by UTIs was 0.700 (95% CI, 0.628-0.772). The maximum Youden index was calculated to be 0.36, corresponding to an optimal cutoff value of 0.0965 ng/L on the ROC curve.ConclusionEscherichia coli and Candida glabrata are the predominant pathogens in T2DM patients with UTIs. Serum PCT levels have moderate value in the diagnosis of patients with T2DM complicated by UTIs.